Improving Physical Fitness with a Circuit Training Approach at State Vocational High School 1 Lamongan - Ahmad Faris Dwinanda Saputra; Tjahyo, Bambang Ferianto; Purnama, Tri Hadi (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
This research is classroom action research to increase the level of physical fitness of students with a circuit training approach in class XI Financial Accounting Institute 1 SMK Negeri 1 Lamongan. Based on the nutritional status of students in the average normal category with a Body Mass Index (BMI) result of 19.69 and a percentage of 43% in the normal category, This classroom action research method is based on the Kemmis and MC Taggart models of research conducted through four stages, including planning, implementing, observing, and subsequent reflection. The four stages become a cycle. Data collection used the Multistage Fitness Test (MFT) instrument and used descriptive analysis techniques to describe the percentage data from the Multistage Fitness Test (MFT) results obtained from cycles 1 and 2, with a total of 35 students. The results of the physical fitness research experienced an increase. The percentage of 60% in the very poor category in cycle 1 decreased to 28% in cycle 2, while in cycle 1, which was originally 0% in the good category, it increased by 3%. So the results of cycles 1 and 2 have increased even though they are still in the less category, so further action is needed in learning in class XI Financial Accounting at SMK Negeri Lamongan. So it can be concluded that the circuit training approach can improve the physical fitness of students.